The Copywriting of Palembang Bird Park as a Tourism Destination in Palembang - Utami, Wahyuni Dianita; Simanjuntak, Tiur; Agustinasari, Evi (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2024)
This study explores the creation of a compelling copywriting script designed to promote the Palembang Bird Park. The methodology employed a systematic approach, encompassing idea generation, outline creation, research, material selection, message planning, structural arrangement, script drafting, testing, and finalization. Expert consultations were integral throughout the process, ensuring thoroughness and effectiveness. Data were gathered via observations and interviews, facilitating informed script development. Rigorous testing ensued, involving feedback from experts to refine content and language use. The outcome is a meticulously crafted script titled â€œPalembang Bird Park as a Tourism Destination in Palembang,â€ poised to captivate audiences and make a copywriting script to promote Palembang Bird Park.